The Night Before Christmas at Dunder Mifflin - Baumgartner, Brian; Silverman, Benjamin, 1970-; Gourmelen, Mael (New York : Mariner Books, 2024)
It's Christmas Eve at Dunder Mifflin and Michael Scott is missing, leaving the office to be surprised by a Santa and his beet-loving elf who sneak in with absurd gifts, tacky decorations, and a holiday spirit that promises an unforgettable holiday.
new book 2024 fall.
Keywords: Santa Claus -- (Fictitious character) -- Poetry; Office (Television program : U.S.) -- Poetry; Christmas poetry; Humorous poetry